2020
DOI: 10.3389/fncel.2020.00069
|View full text |Cite
|
Sign up to set email alerts
|

Altered Motoneuron Properties Contribute to Motor Deficits in a Rabbit Hypoxia-Ischemia Model of Cerebral Palsy

Abstract: Cerebral palsy (CP) is caused by a variety of factors attributed to early brain damage, resulting in permanently impaired motor control, marked by weakness and muscle stiffness. To find out if altered physiology of spinal motoneurons (MNs) could contribute to movement deficits, we performed whole-cell patch-clamp in neonatal rabbit spinal cord slices after developmental injury at 79% gestation. After preterm hypoxia-ischemia (HI), rabbits are born with motor deficits consistent with a spastic phenotype includi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…Still other studies of geneticallyinduced motoneuron disease in mice revealed changes only in AIS l but no detected change in AIS d , excitability, or firing behavior [18,19]. While the reasons for disparate findings among motoneuron studies are not evident, we suspect some influence from confounding variables introduced by pathological conditions [20][21][22][23][24][25]. In addition, relationships may be misrepresented when AIS geometry and excitability are not measured together from individual motoneurons.…”
Section: Motoneuron Excitability and Ais Geometrymentioning
confidence: 76%
See 1 more Smart Citation
“…Still other studies of geneticallyinduced motoneuron disease in mice revealed changes only in AIS l but no detected change in AIS d , excitability, or firing behavior [18,19]. While the reasons for disparate findings among motoneuron studies are not evident, we suspect some influence from confounding variables introduced by pathological conditions [20][21][22][23][24][25]. In addition, relationships may be misrepresented when AIS geometry and excitability are not measured together from individual motoneurons.…”
Section: Motoneuron Excitability and Ais Geometrymentioning
confidence: 76%
“…Although this finding provides indirect evidence that AIS geometry and excitability covary in motoneurons, a mouse model of motoneuron disease yields changes in AIS geometry that are unaccompanied by any detectable modification of excitability [18,19]. While these studies provide clear evidence of the dynamic nature of AIS geometry, they leave uncertainty about the relationship with motoneuronal excitability, especially given the complex effects that pathological conditions have on multiple properties that affect excitability [20][21][22][23][24][25]. Uncertainty also arises, because AIS geometry and excitability were not measured together in individual motoneurons.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between this hypothetical passive rheobase current and the measured rheobase current was calculated to quantify the influence that active conductances (presumably persistent inward current) have on recruitment. The influence that persistent inward currents (PICs) exert on motoneuron excitability was also estimated in current clamp mode using the injection of a triangular, depolarizing current ramp with 5 second rise and fall times (Durand et al, 2015;Leroy et al, 2015;Li and Bennett, 2003;Steele et al, 2020). Depolarizing current ramps were set to a peak current of 2 times repetitive firing threshold current (determined with a 100pA/s depolarizing current ramp initiated from -60 mV).…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…We subdivided cells into 1 of 4 types based on the firing hysteresis on ascending and descending portions of the ramp (Bennett et al, 1998;Cotel et al, 2009;Durand et al, 2015;Li and Bennett, 2003) (Type 1: Linear, Type 2: Adapting, Type 3: Sustained, Type 4: Counter clockwise). PICs were measured in voltage clamp by injecting a slow depolarizing voltage ramp (10 mV/s from -90 to -10 mV) over 8 seconds (Huh et al, 2021;Quinlan et al, 2011;Steele et al, 2020). PIC onset voltage, voltage at which the peak current occurs (voltage peak), peak current amplitude, and peak current density were measured from post-hoc leak-subtracted traces as in (Quinlan et al, 2011;Steele et al, 2020;Verneuil et al, 2020).…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
See 1 more Smart Citation